COMPANY IMAGE MANAGEMENT - BOKOVETS, VIKTORIA; PYSMENNYI, ROMAN (Herald of Khmelnytskyi National University. Economic sciences, 2022)
The article deals with the essence of the image, its types and impact on competitiveness. Factors influencing the external and internal image of the enterprise are highlighted. Identified the main mistakes managers in image management. Have been formed a number of approaches to enterprise image management. Analysis of the essence and content of these approaches to the formation and management of the image of the company makes it possible to improve the composition of the main factors in the formation of the image of the company and specific methods of managing it at specific stages of the production cycle. Using any approach requires prior diagnosis of current state of the image and the formation on this basis the optimal set of management actions taking into account the characteristics of the company and the environment in which it functions. The enterprise, taking into account consumers and the opinion of society and seeks to form not only a positive image, but also an image that will increase the competitiveness of the market and contribute for increasing its efficiency.